Implementasi Nilai-Nilai Pancasila dalam Ranah Politik - Sabilla, Annisa; Dewi, Dinie Anggraeni (EduPsyCouns: Journal of Education, Psychology and Counseling, 2021)
This study aims to build the latest meaning of Pancasila values ​​in political life in Indonesia. The method used in this study uses a qualitative approach. Sources and data obtained through literature studies from journals and research that has been previously conducted by other researchers. These sources and data are then studied with relevant theories. The results obtained from the research conducted are that the values ​​contained in each Pancasila precept are able to give new ideas to Indonesian political life. Healthy and smart politics and capable of making Indonesia a safe, orderly and harmonious country. However, this can only be realized if all existing values ​​are properly interpreted and implemented by all Indonesian citizens. By upholding and living the values ​​of Pancasila, it really needs to be done. This is none other than for the sake of the survival of the nation and state of Indonesia.